Overweight, Obesity and High Blood Pressure: Early Atherogenic Signs in Children Aged 3 to 7 Years - Auza-Santivañez, Jhossmar Cristians; Bautista-Vanegas, Freddy Ednildon; Cabezas-Soliz, Ingrid Neysa; Quisbert Vasquez, Henrry Temis; Zelaya-Espinoza, Yenifer; Márquez-Molina, Jorge; Espejo-Alanoca, Delly; Barrientos Lujan, Paola Kattya; Santander Oberson, Isaura (Multidisciplinar (Montevideo), 2025)
Introduction: Human atherosclerosis has been considered for centuries as one of the greatest predators of health, its distribution on the planet is so wide that it overwhelmingly surpasses any other pathological process and reaches epidemic proportions, both in economically developed populations and in the process of becoming so.Objective: To identify the presence of overweight, obesity and arterial hypertension as early signs of atherosclerosis in children aged 3-7 years.Methods: A descriptive-analytical cross-sectional epidemiological study was carried out in 5 clinics of the "19 de abril" University Polyclinic, in the Plaza de la Revolución municipality, Havana City, during the period 2022-2023. The sample consisted of 152 children aged 3 to 7 years who met the inclusion criteria. The data were collected using the new model (AtecomR) and stored in an automated database in Microsoft Access. Statistical processing was performed using the SPSS statistical package, through a Toshiba Intel (R) Pentium IV microprocessor.Conclusion: This study constitutes a preamble for other investigations that address the problem of cardiovascular disease from the perspective of intrauterine life. The results have provided certain evidence, which, together with a review of the literature, has allowed us to propose the following conclusions. A high frequency of obesity, overweight and high blood pressure levels was identified in the study population. It was observed that in the obese and overweight group they had a tendency to increase with age, being higher their frequency between five and six years respectively. It was shown that overweight and obesity in children were factors for the presence of alterations in blood pressure.